Static Load Test on Trapezoidal Filling Structure of Crushed Concrete Particles Reinforced with Waste Tire Slices - Fang Tong; Qiang Ma; Bin Hu; Zhenyi Zheng (Advances in Civil Engineering)
In this paper, a series of model tests about the trapezoidal filling structures filled with tire reinforced concrete particles has been conducted to study their stability and the ultimate bearing capacity. The effects of the reinforcing tire slices on the global stability and ultimate bearing capacity of the model were investigated, the results show that the tire slices reinforcement can reduce the total settlement of the trapezoidal filling structure, and the ultimate bearing capacity of the reinforced trapezoidal filling structure with tire slices is obviously improved. Among them, the settlements of crushed concrete particles reinforced with bottom layer, top layer, and two layers (both bottom layer and top layer) waste tire slices are 11.5%, 37.7%, and 46.2% less than that of unreinforcement, respectively. Compared with unreinforcement, when the top layer of the model is reinforced with tire slices, the Earth pressure values at the top layer and the bottom layer are reduced by 21.1% and 22.7%, respectively; the Earth pressure values at the top layer and the bottom layer are reduced 6.3% and 14.3%, respectively, when the bottom layer of the model is reinforced with tire slices, and the Earth pressure values at the top layer and the bottom layer are reduced 23.4% and 32.9%, respectively, when the two layers of the model are reinforced with tire slices. The sliding surface of the pure concrete particles filled trapezoidal structure is continuous and runs through the whole trapezoidal filling structure slope; the sliding zone of reinforced trapezoidal filling structure with tire slices decreases with the laying of tire slices.